Plasmon-enhanced Fields and Upconversion Luminescence utilizing Earth-abundant Plasmonic Nanoparticles - Kalejaiye, Akorede (My University, 2021)
This short review paper describes how earth-abundant plasmonic nanoparticle (specifically Magnesium, Aluminium and Sodium nanoparticles), which have not been given much attention possess advantages over conventional plasmonic particles, and can be used to achieve efficient upconversion luminescence – the enhancement of low energy excitations - due to their availability and stability. They can be used to achieve high upconversion luminescence efficiency by coupling their plasmonic resonances with the upconversion particles due to their localized field enhancement effect. Copper nanoparticles just like any other plasmonic nanoparticles can be used for Metal Enhanced Fluorescence. A major advantage of Earth abundant nanoparticles is that they are more stable and readily available to be used in industrial applications for example in photovoltaic cells.
Keywords: earth abundant metals; metal enhanced fluorescence; plasmons; upconversion luminescence